Factor 8x^3+22x^2-6x/4x-1

<-- Enter Expression you want factored

Factor the rational expression below:
8x3 + 22x2 - 6x
4x - 1

We do this by factoring numerator and denominator separately first

Factor 8x3 + 22x2 - 6x

Evaluating the expression you entered, we can factor out a term of 2x
Factor out 2x from 8x3
Our new constant becomes 8 ÷ 2 = 4
Our new x variable piece becomes: x(3 - 1) = x2
Our new term becomes 4x2

Factor out 2x from 22x2
Our new constant becomes 22 ÷ 2 = 11
Our new x variable piece becomes: x(2 - 1) = x1
Our new term becomes 11x

Factor out 2x from -6x
Our new constant becomes -6 ÷ 2 = -3
Our new x variable piece becomes: x(1 - 1) = x0 = 1
Our new term becomes -3

Our factored expression is as follows:
2x(4x2 + 11x-3)



Attach our factored out piece from the beginning of our calculation for our final expression:
2x(4x2 + 11x - 3)

Factor 4x - 1


Our factored out term becomes:
(4x - 1)

Our factored rational expression is as follows:
2x(4x2 + 11x - 3)
(4x - 1)